A System for Evaluation of Human Driving Based on IoT and Computer Vision - Janjić, Đordje (E-business technologies conference proceedings, 2021)
Object of research in this paper is human driving. The primary goal of this research is to simplify and improve driver education for newcomers. This is achieved through combination of technologies and libraries in Python. OpenCV is used for computer vision, which predicts and observes traffic participants via Raspberry Pi microcomputer and its camera. Haar Cascade is object detection algorithm that gives the ability to software to detect objects of interest for evaluating human compliance with traffic rules.